Pembangunan Perangkat Lunak Multimedia Berbasis Android Untuk Pembelajaran Perangkat Keras Komputer Menggunakan MDLC - Harya Bima Dirgantara (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
The purpose of the research conducted is to develop a software application for learning media to introduce computer hardware based on Android, this learning media is very suitable for people who do not understand about computer hardware. The method for conducting research and designing the software uses the MDLC method or stands for Multimedia Development Life Cycle, this method is very appropriate and suitable to support the research. The Android-based application is designed with the Java programming language, because the basic programming language of the application is made. The expected result of this research is that the application will be useful for the general public or students who want to learn about computer hardware.